Project Eagle the top-secret OSS operation that sent Polish spies behind enemy lines in World War II - Micgiel, John S. (Stackpole Books, 2024)
"Project Eagle tells the fascinating but little-known World War II story of Polish soldiers recruited from POW camps and trained to go behind German lines for intelligence gathering and espionage missions that would assist the Allies in their invasion of Germany and help bring the war to an end."